INTERNALIZATION OF MORAL VALUES IN CULTIVATING ANTI-CORRUPTION CHARACTER AT PESANTREN - Subna El Hidayah; Mohammad Takdir; Tatimmatul Umah (Living Sufism: Journal of Sufism and Psychotherapy, 2023)
Corrupt behavior occurs not only outside educational institutions but also within the pesantren environment, which functions as a setting for acquiring religious knowledge. This study aims to clarify the assimilation of moral ideas among students in fostering an anti-corruption character at the Annuqayah Islamic boarding school. This study utilizes a qualitative field methodology comprising observation, interviews, and documentation techniques. The data analysis method utilizes the Miles and Huberman approach. The findings of this study identify three categories of moral principles that should be strengthened in students' character: understanding of morals, religion, and sharia. The factors affecting the establishment of moral principles in students arise from compliance and resistance to pesantren norms. The methodology utilized to instill anti-corruption ideals at the Annuqayah Islamic boarding school encompasses the dissemination of fundamental information through faith, ethics, and morals, the cultivation of discipline, and the promotion of respect for elders and compassion for the youth.